2012
DOI: 10.1179/1743676112y.0000000015
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic deposition of apatite type lanthanum silicates for SOFC half cell production

Abstract: Apatite type lanthanum silicates (ATLS) are a new class of electrolyte materials exhibiting good oxygen ion conductivity in the intermediate temperature range. Electrophoretic deposition of aluminium doped ATLS powders from a non-aqueous solvent on a conductive polymer substrate was assessed by carefully adjusting the charging agent and polyelectrolyte addition. A modified electrode was built to be able to deposit on the non-conductive substrate. The optimised suspension was used to assess the feasibility of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Nowadays new synthesis processes are applied to alleviate the calcination conditions and reduce the production cost. In recent years, sol-gel synthesis methods (18)(19)(20)(21)(22)(23)(24) have become a research focus in consideration of its relatively low cost and simple implementation after the pioneer work carried out by Tao et al (17).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays new synthesis processes are applied to alleviate the calcination conditions and reduce the production cost. In recent years, sol-gel synthesis methods (18)(19)(20)(21)(22)(23)(24) have become a research focus in consideration of its relatively low cost and simple implementation after the pioneer work carried out by Tao et al (17).…”
Section: Introductionmentioning
confidence: 99%
“…used EPD technique to develop porous LSM/LSM‐YSZ cathode layers onto a carbon‐sputtered surface of dense zirconia sheet. Recently, Jothinathan et al . successfully demonstrated the uniform deposition of aluminum‐doped lanthanum silicate directly onto the porous anode substrate using a conducting polymer substrate as the backing electrode.…”
Section: Introductionmentioning
confidence: 99%
“…These pictures indicates that the lanthanum silicate film is relatively dense and the thickness is about 10¯m which is less than the value in the previous work with the EPD. 22) Although we have to use an appropriate substrate in order to apply the EPD film to IT-SOFC, it can be concluded that our strategy is one of the easy promising ways to manufacture a dense thin film of the lanthanum silicate.…”
Section: Electrophoretic Depositionmentioning
confidence: 99%
“…As for the powder-synthesis process, some liquid-based methods, such as a solgel method, 6)8) a coprecipitation method, 9)11) an urea-nitrates combustion, 12) a molten-salt synthesis, 13) and a hydrothermal method, 14) succeeded in a preparation of the nanopowder at relatively low temperature. Previous works also applied an alcoxide-hydrolysis method, 15) a plasma spray synthesis, 16)18) a magnetron sputtering, 19),20) a spin coating 21) and an electrophoretic deposition using powder prepared by a solgel process, 22) for a film preparation of the lanthanum silicates. In general, however, most of these processes cannot be considered as a simple process, and thus another strategy for manufacturing of the dense film electrolyte is still expected highly at the moment.…”
Section: )5)mentioning
confidence: 99%